Perceptions of Science Communication’s Domain, Practices, and Identity: What Concerns Members on the Peripheral Edge of a Community of Practice - Rebecca Swenson; Corissa Marson (Journal of Applied Communications, 2024)
This research shares insights from qualitative interviews with scientists in agricultural and environmental science programs (n=26) to better understand how occasional, peripheral, or emerging members of the science communication community of practice perceive its domain, practices, and identity. Findings suggest concern about personal risks of communicating, especially control over messaging, interactions with disagreeable audiences, being incorrect, and reputation damage. However, many believe that communication is broadly important for their field and resources. Scientists did not have clear agreement on boundaries of science communication, and advocacy and uncertainty were points of contention. Suggestions for strengthening science communication training are proposed.
Keywords: science communication; training; interviews; curriculum; identity